Resin composition and application thereof

By adding high DK first fillers, high -heat guidance second fillers, and molybdenum compounds to the thermosettic resin, optimize the proportion of the fillers of the resin composition, solve the problem of heat accumulation and high -agency constant board development problem in electronic equipment, and achieve high Performance resin composition is suitable for high -frequency antenna substrate modules.

CN119371822APending Publication Date: 2025-01-28SHENGYI TECH (CHANGSHU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411501282.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In modern electronic devices, high frequency and high power components lead to heat accumulation, resulting in increased equipment temperature, reduced component performance or damage, and the development of high dielectric constant substrates is difficult to meet the needs of high-frequency communication equipment.

Method used

A resin composition, including thermosetry resin, multiple fillers and molybdenum compounds. By optimizing the types and proportion of the filler, the thermal conductivity, the dielectric constant, the damp -resistant and drilling of the resin composition, the dielectric constant, the dampness constant, the humidity and thermal heat resistance, and the drilling properties.

Benefits of technology

Achieve high heat resistance, high heat guidance, high -agency constant and good humidity resistance and drilling processability. It is suitable for high -frequency antenna substrate modules, especially the requirements of the millimeter wave antenna module.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371822A_ABST
    Figure CN119371822A_ABST
Patent Text Reader

Abstract

The invention provides a resin composition and application thereof. The resin composition comprises the following components in parts by weight: 60-200 parts of thermosetting resin; 10 to 100 parts by weight of a first filler, wherein the Dk of the first filler under 10GHz is 5 to 200; 1-150 parts by weight of a second filler, wherein the thermal conductivity of the second filler is 20-300 W / m.K; 0.5-15 parts by weight of a third filler, wherein the third filler is a molybdenum compound; and the thermosetting resin contains at least one of the following structures: # imgabs0 # imgabs1 #. On the basis of meeting higher heat resistance, the heat conductivity coefficient, dielectric constant, heat and humidity resistance and drilling processability of the resin composition are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic materials, and in particular to a resin composition and application thereof. Background Art

[0002] On the one hand, with the rapid development of modern communication technology, the operating frequency of electronic equipment is getting higher and higher, and the heat generation is getting higher and higher. Moreover, with the continuous development of PCB towards high density and multi-layer, the space for mounting and installing components on PCB is greatly reduced. The power requirements of power components of complete electronic products are getting higher and higher. Small space and high power will inevitably generate more heat accumulation. If the accumulated heat cannot be discharged in time, the operating temperature of the equipment will increase. In the long run, the electrical performance of the components will be reduced or even damaged, seriously damaging the life and reliability of the equipment.

[0003] On the other hand, radio navigation is developing rapidly and the mobile communication market is becoming increasingly open, which has led to the rapid development of various positioning and navigation systems, such as vehicle positioning, communication positioning, remote control mapping, and electronic navigation, and has been continuously miniaturized. However, the size of the RF front-end device is inversely proportional to the dielectric constant of the substrate, so the development of high dielectric constant substrates is imperative. At the same time, the fields of high-frequency communication equipment, frequency converters, and piezoelectric sensors are developing rapidly, and the demand for high dielectric constant substrates is increasing, and the development of high dielectric constant substrates is highly anticipated. Summary of the invention

[0004] The purpose of the present invention is to provide a resin composition and application thereof.

[0005] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a resin composition, comprising:

[0006] Thermosetting resin: 60-200 parts by weight;

[0007] First filler: 10-100 parts by weight, wherein the Dk of the first filler at 10 GHz is 5-200;

[0008] Second filler: 1-150 parts by weight, the thermal conductivity of the second filler is 20-300 W / mK;

[0009] The third filler: 0.5-15 parts by weight, wherein the third filler is a molybdenum compound;

[0010] The thermosetting resin contains at least one of the following structures:

[0011]

[0012] As a further improvement of the present invention, the thermal conductivity of the thermosetting resin cured product is 0.1-2.5 W / mK.

[0013] As a further improvement of the present invention, the thermosetting resin includes at least two of maleimide resin, cyanate resin and epoxy resin.

[0014] As a further improvement of the present invention, the thermosetting resin includes maleimide resin and cyanate resin; or, the thermosetting resin includes maleimide resin and epoxy resin.

[0015] As a further improvement of the present invention, the average particle size ratio of the first filler, the second filler and the third filler is (0.1-5): (5-20): (0.5-5).

[0016] As a further improvement of the present invention, the ratio of the thermal conductivity of the mixture of the first filler and the second filler to the thermal conductivity of the thermosetting resin is 80-300.

[0017] As a further improvement of the present invention, the first filler is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate, and lead lanthanum zirconate titanate; and / or, the second filler is selected from at least one of aluminum nitride, boron nitride, and silicon nitride; and / or, the molybdenum compound is selected from at least one of pure zinc molybdate, pure calcium molybdate, calcium molybdate-coated talc, zinc molybdate-coated silica, zinc molybdate-coated talc, zinc molybdate-coated montmorillonite, silica-coated zinc molybdate, silica-coated ammonium zinc molybdate, Zn3Mo2O8(OH)2, (NH4)Zn2MO9·(H2O), dialkyl dithiocarbamate molybdenum, ammonium octamolybdate, molybdenum disulfide, or dialkyl dithiophosphorosulfide molybdenum oxide.

[0018] As a further improvement of the present invention, the weight ratio of the first filler to the second filler is 0.1-1.

[0019] As a further improvement of the present invention, the first filler, the second filler and the third filler are all surface treated with a silane coupling agent.

[0020] To achieve the above-mentioned object of the invention, the present invention also provides a use of the above-mentioned resin composition in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0022] The resin composition of the present invention adds three different types of fillers to a thermosetting resin with high thermal conductivity, including a first filler with high Dk, a second filler with high thermal conductivity, and a molybdenum compound. The resin composition has good compatibility during the mixing process and can increase the filling amount of the filler. On the basis of meeting a relatively high heat resistance, the thermal conductivity, dielectric constant, moisture and heat resistance, and drilling processability of the resin composition are further improved. Thus, a cured product with high heat resistance, high thermal conductivity, high dielectric constant, good moisture and heat resistance, and drilling processability can be finally obtained, that is, a cured product with relatively excellent comprehensive performance can be obtained, which can be well applied in the field of high heat-resistant high-frequency antenna substrate modules, especially can meet the requirements of millimeter wave antenna modules. DETAILED DESCRIPTION

[0023] The following is a specific implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this field, several improvements and modifications can be made without departing from the principles of the embodiment of the present invention. These improvements and modifications are also considered to be within the scope of protection of the embodiment of the present invention.

[0024] The terms “comprising” and “containing” in the present specification mean that other components may be contained in addition to the components mentioned above, and these other components can impart different characteristics to the resin composition.

[0025] The present invention provides a resin composition, comprising:

[0026] Thermosetting resin: 60-200 parts by weight;

[0027] First filler: 10-100 parts by weight, wherein the Dk of the first filler at 10 GHz is 5-200;

[0028] Second filler: 1-150 parts by weight, the thermal conductivity of the second filler is 20-300 W / mK;

[0029] The third filler: 0.5-15 parts by weight, wherein the third filler is a molybdenum compound;

[0030] The thermosetting resin contains at least one of the following structures:

[0031]

[0032]

[0033] The resin composition of the present invention adds three different types of fillers to a thermosetting resin with high thermal conductivity, including a first filler with high Dk, a second filler with high thermal conductivity, and a molybdenum compound that can make the final cured product have good moisture and heat resistance and drilling processability. The resin composition has good compatibility during the mixing process and can increase the filling amount of the filler. On the basis of meeting higher heat resistance, the thermal conductivity, dielectric constant, moisture and heat resistance and drilling processability of the resin composition are further improved. Therefore, a cured product with high heat resistance, high thermal conductivity, high dielectric constant, good moisture and heat resistance and drilling processability can be finally obtained, that is, a cured product with excellent comprehensive performance can be obtained, which can be well used in the field of high heat-resistant high-frequency antenna substrate modules, especially can meet the requirements of millimeter wave antenna modules.

[0034] It should be noted that the cured product in the present invention can be understood as a prepreg, an insulating film, an insulating board, a copper-clad laminate, a circuit substrate, an electronic device, and the like.

[0035] In some optional embodiments, the thermosetting resin includes at least two of maleimide resin, cyanate resin, and epoxy resin.

[0036] In a specific embodiment of the thermosetting resin, the thermosetting resin includes maleimide resin and cyanate resin. Specifically, the thermosetting resin is a composite resin composed of maleimide resin and cyanate resin, and the weight ratio of maleimide resin to cyanate resin is (50-140): (10-60), which can make the final cured product have high heat resistance and high modulus.

[0037] The maleimide resin is at least one of the following structural formulas:

[0038]

[0039]

[0040] R2 is hydrogen, methyl or ethyl, R1 is methylene, ethylene or n is an integer from 1 to 10;

[0041]

[0042] n is an integer from 1 to 10;

[0043] n is an integer from 1 to 10;

[0044] R is hydrogen, methyl or ethyl, and n is an integer from 1 to 10;

[0045]

[0046] In a preferred embodiment, the maleimide resin is at least one of the above structural formula (3), structural formula (7) and structural formula (9), and has high thermal conductivity.

[0047] The cyanate resin is selected from bisphenol A cyanate, biphenyl cyanate, terphenyl cyanate, DCPD cyanate, phenolic cyanate, bisphenol E cyanate, bisphenol F cyanate, bisphenol M cyanate, naphthalene cyanate, azomethyl cyanate, ester cyanate or containing group At least one of the cyanate esters.

[0048] In a preferred embodiment, the cyanate ester is at least one of biphenyl cyanate ester, terphenyl cyanate ester or azomethyl cyanate ester.

[0049] In another specific embodiment of the thermosetting resin, the thermosetting resin includes maleimide resin and epoxy resin, and has high thermal conductivity. Specifically, the thermosetting resin is a composite resin composed of maleimide resin and epoxy resin, and the weight ratio of maleimide resin to epoxy resin is (30-120): (30-80).

[0050] The epoxy resin is selected from bisphenol A epoxy resin, bisphenol F epoxy resin, naphthalene epoxy resin, phosphorus-containing epoxy resin, o-cresol epoxy resin, bisphenol A novolac epoxy resin, phenol novolac epoxy resin, trifunctional phenol epoxy resin, bisphenol ether epoxy resin, tetraphenylethane epoxy resin, biphenyl epoxy resin, terphenyl epoxy resin, azomethyl epoxy resin, dicyclopentadiene epoxy resin, ester epoxy resin, aralkyl linear novolac epoxy resin, alicyclic epoxy resin, glycidylamine epoxy resin, glycidylester epoxy resin or containing the following groups At least one of the epoxy resins.

[0051] In some preferred embodiments, the epoxy resin is selected from biphenyl epoxy resin, terphenyl epoxy resin, azomethyl epoxy resin or bisphenol ether epoxy resin.

[0052] In some optional embodiments, the thermal conductivity of the cured thermosetting resin is 0.1-2.5 W / mK, which means it has high thermal conductivity.

[0053] In a preferred embodiment, the thermal conductivity of the cured thermosetting resin is 0.2-1.5 W / mK.

[0054] Specifically, the thermal conductivity of the cured thermosetting resin material mentioned above refers to the cured resin material when the resin composition does not contain a filler.

[0055] In some optional embodiments, the ratio of the thermal conductivity of the mixture of the first filler and the second filler to the thermal conductivity of the thermosetting resin is 80-300, and the heat dissipation between the inorganic and organic substances is better, thereby effectively improving the thermal conductivity of the final cured product, and can be well used in the field of high-heat-resistant high-frequency antenna substrate modules, especially meeting the requirements of millimeter-wave antenna modules.

[0056] In some optional embodiments, the average particle size ratio of the first filler, the second filler and the third filler is (0.1-5): (5-20): (0.5-5). The average particle size of the first filler and the third filler is set to be smaller, while the average particle size of the second filler with high thermal conductivity is set to be larger. The filler with smaller particle size is easy to disperse into the space between the high thermal conductivity fillers with larger particle size, which not only increases the filling amount of the filler, but also improves the thermal conductivity of the substrate. At the same time, the uniform dispersion of the small particle size filler suppresses the decrease of the Dk value and thermal conductivity, improves the peel strength and moisture and heat resistance, and effectively improves the drilling processability of the final cured product to meet the requirements of the millimeter wave antenna module.

[0057] Specifically, the first filler is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate, and lead lanthanum zirconate titanate. The second filler is selected from at least one of aluminum nitride, boron nitride, and silicon nitride. The molybdenum compound is selected from at least one of pure zinc molybdate, pure calcium molybdate, calcium molybdate-coated talc, zinc molybdate-coated silica, zinc molybdate-coated talc, zinc molybdate-coated montmorillonite, silica-coated zinc molybdate, silica-coated ammonium zinc molybdate, Zn3Mo2O8(OH)2, (NH4)Zn2MO9·(H2O), dialkyl dithiocarbamate molybdenum, ammonium octamolybdate, molybdenum disulfide, or dialkyl dithiophosphorosulfide molybdenum oxide.

[0058] In some optional embodiments, the weight ratio of the first filler to the second filler is 0.1-1, so that the final cured product can maintain a relatively high thermal conductivity while improving the Dk value and satisfying better drilling processability.

[0059] In a preferred embodiment, the first filler, the second filler and the third filler are all surface treated with a silane coupling agent. The compatibility between the three fillers can be improved, which not only increases the filling amount of the filler, but also maintains excellent dispersibility and excellent high dielectric constant, high thermal conductivity and drilling processability of each, so that the resin composition has excellent high dielectric constant, high thermal conductivity and drilling processability, and can be well used in the field of high heat-resistant high-frequency antenna substrate modules to meet the requirements of 5G millimeter wave antenna modules.

[0060] Specifically, the silane coupling agent is selected from at least one of an epoxy silane coupling agent, an amino silane coupling agent, a vinyl silane coupling agent, a methacrylate silane coupling agent or a mercapto silane coupling agent.

[0061] Furthermore, the resin composition further comprises 5-60 parts by weight of a curing agent. Specifically, the curing agent is selected from at least one of phenolic resin, dicyandiamide, aromatic diamine compounds, acid anhydride compounds, and active ester compounds.

[0062] In a preferred embodiment, the curing agent is selected from phenolic resin or active ester compound.

[0063] Furthermore, the resin composition further comprises 0.01-10 parts by weight of a catalyst, wherein the catalyst is at least one selected from imidazoles, pyridines, organic phosphorus or metal salts.

[0064] Preferably, the imidazole catalyst is selected from at least one of 4-dimethylaminopyridine, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, modified imidazole and zinc octanoate.

[0065] Preferably, the organophosphorus is selected from triphenylphosphine.

[0066] Furthermore, the resin composition also contains 5-60 parts by weight of a flame retardant, so that the final cured product has a certain flame retardant effect.

[0067] The flame retardant is selected from at least one of a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, an organic silicon flame retardant, and an organic metal salt flame retardant.

[0068] Specifically, the bromine flame retardant is selected from decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide; the phosphorus flame retardant is selected from inorganic phosphorus, condensed phosphate ester, phosphoric acid, hypophosphite, phosphorus oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ), (k is an integer from 1 to 5), 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,6-dimethylphenyl)phosphine, phosphazene, modified phosphazene.

[0069] In a preferred embodiment, the flame retardant is a condensed phosphate ester, a hypophosphite or a bis-DOPO compound.

[0070] Furthermore, the present invention also provides a use of the above resin composition in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.

[0071] Specifically, the present invention further provides a prepreg, which comprises a reinforcing material and the above-mentioned resin composition, wherein the resin composition is impregnated on the reinforcing material.

[0072] The reinforcing material may be selected from at least one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fabrics.

[0073] Preferably, the reinforcing material is glass fiber cloth. Among the glass fiber cloth, open fiber cloth or flat cloth is preferably used. More preferably, the glass fiber cloth is E glass fiber cloth, S glass fiber cloth, T glass fiber cloth or Q glass fiber cloth.

[0074] In addition, when the reinforcing material is glass fiber cloth, the glass fiber cloth generally needs to be chemically treated to improve the interface bonding between the resin composition and the glass fiber cloth. The main method of the chemical treatment is coupling agent treatment, and the coupling agent used is preferably epoxy silane coupling agent or amino silane coupling agent, so that the reinforcing material has good water resistance and heat resistance.

[0075] Specifically, the method for preparing the prepreg comprises the following steps:

[0076] Dissolving the resin composition with a solvent to prepare a resin composition glue solution;

[0077] The reinforcing material is immersed in the above-mentioned resin composition glue solution, and then the immersed reinforcing material is taken out and heated and dried to obtain the prepreg.

[0078] In a specific embodiment, the impregnated reinforcing material is baked at 100° C. to 180° C. for 1 min to 15 min, and the prepreg is obtained after drying.

[0079] Specifically, the solvent can be selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene, and cyclohexane.

[0080] The present invention does not specifically limit the amount of solvent used in preparing the prepreg. The amount of solvent added is selected by those skilled in the art based on their own experience, as long as the obtained resin composition glue has a viscosity suitable for use.

[0081] The present invention also provides a copper-clad laminate, which comprises at least one of the above-mentioned prepregs and a metal foil formed on at least one side of the prepreg. When the copper-clad laminate comprises only one of the above-mentioned prepregs, the metal foil is arranged on at least one side of the surface of the prepreg. When the copper-clad laminate comprises at least two of the above-mentioned prepregs, the at least two prepregs are stacked and bonded together by heating and pressurizing to form a combined sheet, and then the metal foil is bonded on one side or both sides of the combined sheet by heating and pressurizing to form the copper-clad laminate.

[0082] Specifically, the preparation steps of the copper-clad laminate are as follows: a single side or double sides of a prepreg is coated with metal foil, or at least two prepregs are stacked to form a combined sheet, a single side or double sides of the combined sheet is coated with metal foil, and hot pressing is performed to obtain a copper-clad laminate.

[0083] The pressing conditions of the copper-clad laminate are: pressing at a pressure of 0.2 to 2 MPa and a temperature of 150° C. to 250° C. for 1 to 4 hours.

[0084] Specifically, the number of the prepregs can be determined according to the required thickness of the copper-clad laminate, and one or more prepregs can be used.

[0085] The metal foil may be copper foil or aluminum foil, and its material is not limited; the thickness of the metal foil is not particularly limited, such as 5 μm, 8 μm, 12 μm, 18 μm, 35 μm or 70 μm.

[0086] The present invention also provides an insulating plate, which comprises at least one of the aforementioned prepreg sheets.

[0087] The present invention also provides an insulating film, which comprises a carrier film and the aforementioned resin composition coated thereon, and can significantly improve the heat resistance of the insulating film.

[0088] The preparation method of the insulating film is as follows: dissolving the resin composition with a solvent to prepare a resin composition glue solution, then coating the resin composition glue solution on a carrier film, and heating and drying the carrier film coated with the resin composition glue solution to obtain the insulating film.

[0089] In a specific embodiment, the carrier film coated with the resin composition glue is baked at 100° C. to 160° C. for 3 min to 10 min, and the insulating film can be obtained after drying.

[0090] The solvent is selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene and cyclohexane.

[0091] The carrier film is selected from at least one of PET film, PP film, PE film and PVC film.

[0092] The present invention also provides a circuit substrate, which includes one or more of the aforementioned prepreg, copper-clad laminate, insulating plate, and insulating film.

[0093] The present invention also provides an electronic device, which includes the aforementioned circuit substrate.

[0094] The present invention will be described in detail below with reference to specific embodiments; of course, it is to be understood that the embodiments of the present invention are not limited to these embodiments.

[0095] Examples 1 to 5 and Comparative Examples 1 to 3:

[0096] The components and contents of the resin compositions of Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Table 1 below:

[0097] Table 1

[0098]

[0099]

[0100] Specifically, the information of each component involved in Table 1 above is shown in Table 2 below:

[0101] Table 2

[0102]

[0103] The preparation method of the resin composition in Examples 1 to 5 and Comparative Examples 1 to 3 is as follows: according to the components and corresponding contents in Table 1, an appropriate amount of butanone is mixed, stirred and mixed, and then diluted to a resin composition glue having a solid content of 65wt%, wherein the solid content of 65wt% is calculated by weight.

[0104] The E glass fiber cloth used as the reinforcing material was pretreated with an epoxy silane coupling agent and then immersed in the resin composition glue obtained in the above Examples 1 to 5 and Comparative Examples 1 to 3, respectively. After being soaked, it was taken out and placed in a 160° C. forced drying oven, and baked for 3 to 6 minutes to obtain the semi-cured sheets corresponding to Examples 1 to 5 and Comparative Examples 1 to 3, respectively.

[0105] Copper-clad laminates corresponding to the above-mentioned embodiments 1 to 5 and comparative examples 1 to 3 were prepared. The method for preparing the copper-clad laminate was as follows: at least two of the above-mentioned semi-cured sheets were cut to 300×300 mm, and the semi-cured sheets were stacked into a composite sheet with a certain stacking structure, and then a 12 μm thick electrolytic copper foil was placed on both sides of the composite sheet, and then placed in a vacuum hot press, and hot pressed for 1.5 h at a pressure of 1.5 MPa and a temperature of 220°C to obtain a copper-clad laminate.

[0106] The copper-clad laminates corresponding to the above-mentioned embodiments 1 to 5 and comparative examples 1 to 3 were used to perform performance tests. Specifically, the performance evaluation method is as follows:

[0107] (1) Glass transition temperature (Tg): tested according to IPC-TM-650 2.4.24.4 using a dynamic mechanical analyzer (DMA) with a heating rate of 10°C / min and a frequency of 10 Hz;

[0108] (2) Thermal conductivity: tested using ASTM D5470-2017 method;

[0109] (3) Dk and Df: Dielectric properties at 10 GHz measured according to IPC-TM-650 2.5.5.5, SPDR;

[0110] (4) Moisture and heat resistance (PCT): Take 3 samples with a length x width of 10 cm x 10 cm and a thickness of 0.8 mm, with the electrolytic copper foil removed from both sides, dry them at 100°C for 2 h, treat them in a pressure cooker at 121°C and 2 atmospheres for 6 h, immerse them in a tin furnace at 288°C for 20 seconds, and visually observe whether there is stratification and blistering;

[0111] (5) Drilling wear rate: Two drill axes with similar effects in a 6-axis drilling machine were selected for drilling. Six new drills were used for each plate, and each drill drilled 6,000 holes. The drill blade was then observed using a testing microscope to measure the wear and retreat of the blade tip. The distance between the intersection of the vertical line and the center axis and the upper edge of the wear was measured as the drill size. The drill wear rate was calculated using the following formula to evaluate the drilling processability:

[0112] Wear rate % = distance between the rear edge of the drilling hole and the center axis / distance between the front edge of the drilling hole and the center axis × 100%.

[0113] The properties of the copper-clad laminates obtained using the prepregs in Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Table 3 below.

[0114] Table 3

[0115]

[0116]

[0117] Example 1 and Comparative Example 3 are compared in parallel. In Example 1, a first filler with high Dk, a second filler with high thermal conductivity, and a molybdenum compound are added to the maleimide resin and cyanate resin system, while only a first filler with high Dk and a second filler with high thermal conductivity are added to the maleimide resin and cyanate resin system in Comparative Example 3. By comparison, it can be seen that the copper-clad laminate prepared by the resin composition in Example 1 has a lower drilling wear rate than that of Comparative Example 3 on the basis that other properties are similar. That is, it has better drilling processability.

[0118] Example 2 and Comparative Example 1 are compared in parallel. In the resin composition of Example 2, a first filler with high Dk, a second filler with high thermal conductivity, and a molybdenum compound are added, while only the second filler with high thermal conductivity and the molybdenum compound are added in Comparative Example 1. By comparison, it can be seen that the copper-clad laminate prepared by the resin composition in Example 2 has a higher Dk and a higher thermal conductivity than that of Comparative Example 1 on the basis that other properties are similar.

[0119] Example 3 and Comparative Example 2 are compared in parallel. In the resin composition of Example 3, a first filler with high Dk, a second filler with high thermal conductivity, and a molybdenum compound are added, while in Comparative Example 2, only the first filler with high Dk and the molybdenum compound are added, and no second filler with high thermal conductivity is added. By comparison, it can be seen that the copper-clad laminate prepared by the resin composition in Example 3 has a higher thermal conductivity than that of Comparative Example 2 on the basis that other properties are similar.

[0120] In parallel comparison of Example 1 and Example 5, the ratio of the thermal conductivity of the mixture of the first filler and the second filler in the resin composition of Example 1 to the thermal conductivity of the thermosetting resin is between 80-300, while the ratio of the thermal conductivity of the mixture of the first filler and the second filler in the resin composition of Example 5 to the thermal conductivity of the thermosetting resin is 350, which is greater than 300. By comparison, it can be seen that the copper-clad laminate prepared by the resin composition of Example 1 has better heat resistance, higher Dk, lower Df, smaller drilling wear rate, and better thermal conductivity than Example 5 on the basis that other properties are similar.

[0121] It can be seen that in the resin composition of the present invention, three different types of fillers are added to the high thermal conductivity thermosetting resin, including a first filler with high Dk, a second filler with high thermal conductivity and a molybdenum compound. The mixing process has good compatibility and can increase the filling amount of the filler. On the basis of meeting higher heat resistance, the thermal conductivity, dielectric constant, moisture and heat resistance and drilling processability of the resin composition are further improved. Therefore, a cured product with high heat resistance, high thermal conductivity, high dielectric constant, good moisture and heat resistance and drilling processability can be finally obtained, that is, a cured product with excellent comprehensive performance can be obtained, which can be well used in the field of high heat-resistant high-frequency antenna substrate modules, especially can meet the requirements of millimeter wave antenna modules.

[0122] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0123] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A resin composition, characterized in that include: Thermosetting resin: 60-200 parts by weight; First filler: 10-100 parts by weight, wherein the Dk of the first filler at 10 GHz is 5-200; Second filler: 1-150 parts by weight, the thermal conductivity of the second filler is 20-300 W / mK; The third filler: 0.5-15 parts by weight, wherein the third filler is a molybdenum compound; The thermosetting resin contains at least one of the following structures:

2. The resin composition according to claim 1, characterized in that: The thermal conductivity of the thermosetting resin cured product is 0.1-2.5 W / mK.

3. The resin composition according to claim 1, characterized in that: The thermosetting resin includes at least two of maleimide resin, cyanate resin and epoxy resin.

4. The resin composition according to claim 3, characterized in that: The thermosetting resin includes maleimide resin and cyanate resin; or, the thermosetting resin includes maleimide resin and epoxy resin.

5. The resin composition according to claim 1, characterized in that: The average particle size ratio of the first filler, the second filler and the third filler is (0.1-5): (5-20): (0.5-5).

6. The resin composition according to claim 1, characterized in that: The ratio of the thermal conductivity of the mixture of the first filler and the second filler to the thermal conductivity of the thermosetting resin is 80-300.

7. The resin composition according to claim 1, characterized in that: The first filler is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate, and lead lanthanum zirconate titanate; and / or, the second filler is selected from at least one of aluminum nitride, boron nitride, and silicon nitride; and / or, the molybdenum compound is selected from at least one of pure zinc molybdate, pure calcium molybdate, calcium molybdate-coated talc, zinc molybdate-coated silica, zinc molybdate-coated talc, zinc molybdate-coated montmorillonite, silica-coated zinc molybdate, silica-coated ammonium zinc molybdate, Zn3Mo2O8(OH)2, (NH4)Zn2MO9·(H2O), dialkyl dithiocarbamate molybdenum, ammonium octamolybdate, molybdenum disulfide, or dialkyl dithiophosphorosulfide molybdenum oxide.

8. The resin composition according to claim 1, characterized in that: The weight ratio of the first filler to the second filler is 0.1-1.

9. The resin composition according to claim 1, characterized in that: The first filler, the second filler and the third filler are all surface treated with a silane coupling agent.

10. Use of the resin composition according to any one of claims 1 to 9 in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.